Curriculum educators' perceived challenges in applying quality assessment criteria - Ngo, Thi-Thuy-Dung; Bao, Ngoc Tran; Thi Tu, Anh Hua; Yen, Nhu Huynh; Khanh Tran, Tuong Thi; Nam, Ha Nguyen (Institute of Advanced Engineering and Science, 2025)
This cross-sectional quantitative study investigates the implementation challenges of national quality assurance (QA) in Vietnam’s higher medical education system, with a focus on faculty engagement and educator perception during medical curriculum redesign. Conducted at Pham Ngoc Thach University of Medicine, a public institution dedicated to professional healthcare qualifications, the study applies the Ministry of Education and Training (MOET) quality assessment framework, which defines 11 standards central to quality assessment implementation in various domains. Results reveal that standard 4 (teaching and learning approach) received the lowest average score, highlighting significant barriers to implementation. Standards 1, 3, and 5 also emerged as areas of concern. Difficulty in applying quality assessment criteria varied by educator characteristics: younger, less experienced faculty with limited academic credentials, and no prior quality assessment training reported greater difficulty, while senior educators with quality assessment training demonstrated higher compliance and ease in application. To strengthen educator compliance and enable effective QA implementation, the study recommends targeted training programs and support resources for faculty, particularly for early-career educators. These findings offer practical guidance for policymakers, administrators, and academic leaders involved in medical curriculum redesign and QA reforms within Vietnam’s higher education landscape.